Early life gut microbiota is associated with rapid infant growth in Hispanics from Southern California. (1st January 2021) - Alderete, Tanya L.; Jones, Roshonda B.; Shaffer, Justin P.; Holzhausen, Elizabeth A.; Patterson, William B.; Kazemian, Elham; Chatzi, Lida; Knight, Rob; Plows, Jasmine F.; Berger, Paige K.; Goran, Michael I.
ABSTRACT: We aimed to determine if the newborn gut microbiota is an underlying determinant of early life growth trajectories. 132 Hispanic infants were recruited at 1-month postpartum. The infant gut microbiome was characterized using 16S rRNA amplicon sequencing. Rapid infant growth was defined as a weight-for-age z-score (WAZ) change greater than 0.67 between birth and 12-months of age. Measures of infant growth included change in WAZ, weight-for-length z-score (WLZ), and body mass index (BMI) z-scores from birth to 12-months and infant anthropometrics at 12-months (weight, skinfold thickness). Of the 132 infants, 40% had rapid growth in the first year of life. Multiple metrics of alpha-diversity predicted rapid infant growth, including a higher Shannon diversity (OR = 1.83; 95% CI: 1.07–3.29; p = .03), Faith's phylogenic diversity (OR = 1.41, 95% CI: 1.05–1.94; p = .03), and richness (OR = 1.04, 95% CI: 1.01–1.08; p = .02). Many of these alpha-diversity metrics were also positively associated with increases in WAZ, WLZ, and BMI z-scores from birth to 12-months (pall <0.05). Importantly, we identified subsets of microbial consortia whose abundance were correlated with these same measures of infant growth. We also found that rapid growers were enriched in multiple taxa belonging to genera such as Acinetobacter, Collinsella, Enterococcus, Neisseria, and Parabacteroides . Moreover, measures of the newborn gut microbiota explained up to an additional 5% of the variance in rapid growth beyond known clinical predictors (R 2 = 0.37 vs. 0.32, p < .01). These findings indicate that a more mature gut microbiota, characterized by increased alpha-diversity, at as early as 1-month of age, may influence infant growth trajectories in the first year of life.